Application Of Cost Of Quality System By Proton Vendors - Lim, Joo Eng (2003)
Globalization is one of the key trends in the business world today. When countries around the globe open their markets upon the implementation of economic integration which may include European Unification (EU) in Europe, North American Free Trade Agreement (NAFT A) for North America, Asia Pacific Economic Corporation (APEC) for Asia Pacific region, Asean Free Trade Area (AFT A) for Asean countries, industries are now faced with new competition. To survive in this global business arena, organizations must increase their competitiveness not only in terms of cost, but it would also be driven by criteria involving quality, reliability, delivery and technology competency. Often companies respond to this highly dynamic business environment by implementing total quality management (TQM). TQM approach focuses on process improvement and the elimination of all forms of waste. One of the key and effective tools to ensure the success adoption of TQM is cost of quality (COQ). Cost of quality system translates quality problems into a common denominator - money, a financial term that is what management sought of to indicate the economic health of the organization.